Comparative Institutional Analysis and Institutional Complexity - Ahmadjian, Christina L. (Journal of Management Studies, 2016)
ABSTRACTFor multinational corporations (MNEs), the ability to navigate institutional complexity is a key to success or failure. MNEs face a complex landscape of national institutional differences in the countries in which they do business, and decisions on how to respond to these differences are very much strategic ones, reflecting agency and management skill. To understand how institutional complexity affects MNE behaviour, it is necessary to examine how institutions vary on a national or societal level and how these affect firm structure and capabilities in both home and host countries.